Effects of Alhagi maurorum Medik polysaccharide derived from different regions on the intestinal immune functions of lambs - Zulikeyan Manafu; Zulikeyan Manafu; Zulikeyan Manafu; Ronglijiao Du; Ronglijiao Du; Xieraili Malajiang; Xieraili Malajiang; Gulimire Abulikemu; Gulimire Abulikemu; Lijun Xue; Lijun Xue; Ayibike Bierdelieke; et al. (Frontiers Media S.A., 2024)
Introduction: Plant polysaccharide are widely studied as potential prebiotics because of their potential to protect and enhance the immunity of lambs.Methods: In this study, the polysaccharide content of Alhagi maurorum Medik from Aksu (AK) and Shanshan (SS) at different cutting periods was determined, and the functions of Alhagi maurorum Medik polysaccharide were investigated to useas an immunomodulator.Results: Our results indicated that the content of Alhagi maurorum Medik polysaccharide is the highest at the maturity stage, and the polysaccharide content of Alhagi maurorum Medik produced in Shanshan area is higher as compared to the Aksu area. The serum IgG, duodenum IgA, TNF-α, IL-4, IL-10 contents, jejunum IgA, TNF-α, IL-4, IL-17 contents, ileum IgA, IL-17 contents, duodenum villus height, crypt depth and jejunum crypt depth of lambs were significantly adjusted in the SS group as compared to CK control group and AK groups (p < 0.05). Furthemore, the sequencing results showed that SS polysaccharide promoted the release of large amounts of IgA and enhanced the immunal function of intestine by regulating the IgA production pathway and B-cell receptor signaling to activate B cells in the T-dependent pathway.Discussion: Altogether, Alhagi maurorum Medik polysaccharide from SS group holds a promising potential to be used as a valuable immunopotentiator for optimizing the immune system of intestine in lambs.